Dinar currency in a Point of Sales System (D-POS) / Mohd Hafifi Mohd Supir and Dziauddin Shariff - Mohd Supir, Mohd Hafifi; Shariff, Dziauddin (2003)
Gold and silver have been used since the beginning of Islam and have been the most stable currency that the world has ever seen. The bimetallic currency cannot be inflated and devalued, thus making it independent from the financial system the world is currently used. The use of dinar will surely cause zero inflation rates and create a balance economic environment. Based on this reason, this project proposes the use of dinar currency card in a point of sale system. The domain of this system is a Point of Sale (POS) and dinar Conversion. POS is the physical location at which goods are sold to customers or cashier counter whereby both hardware and software will be used in an electronic cash register. By introducing an alternative currency named dinar virtually in form of a RFID card, customers can benefits the stability of the gold value. The RFID will be used as the human-machine interaction because of the efficiency and well-known technology that can be used widely nowadays. RFID is a data collection technology that uses electronic tags for storing data. All users will have a RFID card that works just like debit card but the value inside the card are in dinar and Ringgit. All their information is stored in the database and will be displayed as the card is swapped at the card reader. The card is used as mean of transaction in supermarkets. The card will be bought by the customers with initial dinar value and the value can be added by the customer from time to time. All products are using RFID tags as well to enable identification and information storage such as price, product name, expired date, etc. The objectives of this project are to develop a complete currency transaction using a dinar card and to demonstrate the use of dinar currency in the real environment.